Hubungan Pembiasaan Nilai Karakter Islami dan Disiplin Belajar Siswa Berdasarkan Uji Chi-Square - Jasril; Habibi, Mhmd (Journal of Practice Learning and Educational Development, 2026)
The habit of Islamic character values is one of the strategic efforts in shaping the behavior and attitudes of students, including in improving learning discipline. Islamic values such as honesty, responsibility, discipline, and obedience to rules are believed to be closely related to student learning behavior at school. This study aims to determine the relationship between the habit of Islamic character values and student learning discipline. This study used a quantitative approach with a correlational design. Data were collected through questionnaires on the instillation of Islamic character values and student learning discipline. Data analysis techniques used the Chi-Square test to determine the relationship between two categorical variables. The results showed that there was a significant relationship between the instillation of Islamic character values and student learning discipline (p < 0.05). These findings indicate that the better the habit of Islamic character values, the higher the level of student learning discipline. Therefore, the habit of Islamic character values needs to be continuously strengthened as an integral part of the educational process in schools.